Association Between Carotid Bifurcation Geometry and Atherosclerotic Plaque Vulnerability: A Chinese Atherosclerosis Risk Evaluation Study. Issue 5 (May 2020) - Jiang, Peirong; Chen, Zhensen; Hippe, Daniel S.; Watase, Hiroko; Sun, Bin; Lin, Ruolan; Yang, Zheting; Xue, Yunjing; Zhao, Xihai; Yuan, Chun
Abstract : Objective: Carotid bifurcation geometry has been believed to be a risk factor for the initiation of atherosclerosis because of its influence on hemodynamics. However, the relationships between carotid bifurcation geometry and plaque vulnerability are not fully understood. This study aimed to determine the association between carotid bifurcation geometry and plaque vulnerability using magnetic resonance vessel wall imaging. Approach and Results: A total of 501 carotid arteries with nonstenotic atherosclerosis were included from the cross-sectional, multicenter CARE II study (Chinese Atherosclerosis Risk Evaluation). Four standardized carotid bifurcation geometric parameters (bifurcation angle, internal carotid artery planarity, luminal expansion FlareA, and tortuosity Tort2D) were derived from time-of-flight magnetic resonance angiography. Presence of vulnerable plaque, which was characterized by intraplaque hemorrhage, large lipid-rich necrotic core, or disrupted luminal surface, was determined based on multicontrast carotid magnetic resonance vessel wall images. Vulnerable plaques (N=43) were found to occur at more distal locations (ie, near the level of flow divider) than stable plaques (N=458). Multivariable logistic regression showed that the luminal expansion FlareA (odds ratio, 0.45 [95% CI, 0.25–0.81]; P =0.008) was associated with plaque vulnerability after adjustment for age, sex, maximum wall thickness, plaque location, and other geometric parameters. Conclusions: Smaller luminal expansion at carotid bifurcation is associated with vulnerable plaque. The finding needs to be verified with longitudinal studies and the underlying mechanism should be further explored with hemodynamics measurement in the future. Abstract : Supplemental Digital Content is available in the text.